2013
DOI: 10.1007/s00338-013-1069-2
|View full text |Cite
|
Sign up to set email alerts
|

Topography and biological noise determine acoustic detectability on coral reefs

Abstract: Acoustic telemetry is an increasingly common tool for studying the movement patterns, behaviour, and site fidelity of marine organisms, but to accurately interpret acoustic data, the variability, periodicity and range of detectability between acoustic tags and receivers must be understood. The relative and interactive effects of topography with biological and environmental noise have not been quantified on coral reefs. We conduct two long-term range tests (one and four months duration) on two different reef ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 33 publications
6
43
0
1
Order By: Relevance
“…This detection range is in the range of previous reports, which encompass both higher (Hobday & Pincock, 2011;Huveneers et al, 2016) and similar range values (Welsh et al, 2012;Cagua et al, 2013, Stocks et al, 2014. Some other publications have reported a broad range of distances within the same study (How & de Lestang, 2012;Cagua et al, 2013;Gjelland & Hedger, 2013). Although the detection ranges differ extensively between the cited studies, they all concluded that detection range strongly depends upon meteorological and oceanographic environmental variables, on sediment characteristics and on the environment's topographic complexity factors which all influence sound propagation in water.…”
Section: Variables Influencing Detection Probabilitysupporting
confidence: 81%
See 1 more Smart Citation
“…This detection range is in the range of previous reports, which encompass both higher (Hobday & Pincock, 2011;Huveneers et al, 2016) and similar range values (Welsh et al, 2012;Cagua et al, 2013, Stocks et al, 2014. Some other publications have reported a broad range of distances within the same study (How & de Lestang, 2012;Cagua et al, 2013;Gjelland & Hedger, 2013). Although the detection ranges differ extensively between the cited studies, they all concluded that detection range strongly depends upon meteorological and oceanographic environmental variables, on sediment characteristics and on the environment's topographic complexity factors which all influence sound propagation in water.…”
Section: Variables Influencing Detection Probabilitysupporting
confidence: 81%
“…The present study demonstrates that there is a good detection probability up to 200 m, but it quickly reduces beyond this distance. This detection range is in the range of previous reports, which encompass both higher (Hobday & Pincock, 2011;Huveneers et al, 2016) and similar range values (Welsh et al, 2012;Cagua et al, 2013, Stocks et al, 2014. Some other publications have reported a broad range of distances within the same study (How & de Lestang, 2012;Cagua et al, 2013;Gjelland & Hedger, 2013).…”
Section: Variables Influencing Detection Probabilitysupporting
confidence: 79%
“…The absence of CPDI from the Jupiter study site detection range profile is consistent with the results of Cagua et al [13]. They found, in a high ambient noise coral reef environment, the highest detection proportion occurred at 0 m distance, with progressively decreasing proportions thereafter, for both V16-H and V13-H tags.…”
Section: Discussionsupporting
confidence: 80%
“…Cagua et al. () performed robust range‐testing at two sites on a platform reef in the Red Sea using fixed delay interval V13‐1x (153 dB) and V16P‐6H (160 dB) tags (Cagua et al. ).…”
Section: Discussionmentioning
confidence: 99%